Securing IoT edge device communication with efficient ECC middleware for resource-constrained systems - Mohamed Yusoff, Zainatul Yushaniza; Ishak, Mohamad Khairi; AB Rahim, Lukman (Bulletin of Electrical Engineering and Informatics, 2024)
The internet of things (IoT) rapidly grows into various parts of life. However, it has significant obstacles during setup and deployment, particularly in terms of network segmentation, administration, and security at all tiers, from physical to application. While IoT provides several advanced features and benefits, it is also vulnerable to security threats and flaws that must be thoroughly investigated to avoid misuse. Cryptographic approaches are routinely used to address these security concerns. Message queuing telemetry transport (MQTT), an application layer protocol, is vulnerable to various known and undisclosed security flaws. Integrating encryption techniques within the MQTT protocol to provide secure data flow is a potential strategy for increasing security. This study provides a middleware broker that improves authentication processes, securing connections between cloud servers and resource-constrained devices. Using a Java Servlet and the elliptic curve cryptography (ECC) technique, the study creates a system for creating encrypted identification keys within a web-based transaction framework. This system intends to provide asymmetric authentication that is energy and resource-efficient, with a focus on cost minimization. It also includes a security feature to protect users from common internet threats. The system's efficacy, including its low energy usage of only 4 mJ per device, is thoroughly tested, proving it meets the original protocol criteria.